Cosmic Ray Removal in Fiber Spectroscopic Image. (28th December 2016) - Bai, Zhongrui; Zhang, Haotong; Yuan, Hailong; Carlin, Jeffrey L.; Li, Guangwei; Lei, Yajuan; Dong, Yiqiao; Yang, Huiqin; Zhao, Yongheng; Cao, Zihuang
Abstract: Single-exposure spectra in large spectral surveys are valuable for time domain studies such as stellar variability, but there is no available method to eliminate cosmic rays for single-exposure, multi-fiber spectral images. In this paper, we describe a new method to detect and remove cosmic rays in multi-fiber spectroscopic single exposures. Through the use of two-dimensional profile fitting and a noise model that considers the position-dependent errors, we successfully detect as many as 80% of the cosmic rays and correct the cosmic ray polluted pixels to an average accuracy of 97.8%. Multiple tests and comparisons with both simulated data and real LAMOST data show that the method works properly in detection rate, false detection rate, and validity of cosmic ray correction.